Prevalence, Antimicrobial Susceptibility Pattern and Associated Factors of Staphylococcus Aureus Among Camel's Raw Milk in Babile District, Oromia, Ethiopia - Ahmednur Abdi; Siraj Hussen; Mohammed Ahmed (Veterinary Medicine and Science)
ABSTRACT Background Staphylococcus aureus (S. aureus) is a versatile pathogen that causes diseases. Raw milk is an ideal, rich medium that helps and supports the growth of microorganisms and is highly susceptible to S. aureus immediately after milking. As camel milk was usually consumed in its raw state in pastoralist areas, the contamination and intoxication of raw milk due to pathogenic S. aureus were a public health problem. Objective The study aimed to determine the prevalence, antibiotic resistance pattern, and associated factors of S. aureus in raw camel milk in Babile District, Oromia Region, Eastern Ethiopia. Method A community‐based cross‐sectional study was conducted in the Babille district among 350 raw camel milk. Participants were selected using a multi‐stage sampling technique. Data was collected using a pretested structured questionnaire, and 25 mL of raw camel milk was collected in sterile screw‐capped bottles. S. aureus was identified through culture, Gram stain, and biochemical tests. A bivariate and multivariable logistic regression was done. p‐value ≤ 0.05 was considered statistically significant. Result In this study, the overall prevalence of S. aureus in raw camel milk was 14% (95% CI: 10, 18). Parity [AOR = 3.52, 95% CI: (1.207, 10.277), p = 0.021], drainage condition of the milking place [AOR = 4.62, 95% CI: (1.853, 11.557), p = 0.001], not hand washing before milking [AOR = 3.94, 95% CI: (1.599, 9.716), p = 0.003] and the type of containers used for selling milk [AOR = 8.40, 95% CI: (1.258, 26.068), p = 0.028] were significant predictors of S. aureus. A high level of resistance was recorded against tetracycline (81.6%), penicillin G (81.6%), and amoxicillin (69.4%). Conclusion Overall, the prevalence of S. aureus isolated from raw camel milk of the Babile district was high. Multi‐drug resistance among the isolates was also high. Therefore, washing hands and milking containers before milking and using stainless steel containers instead of plastic containers could be applied. Raw camel milk intended for human consumption should be properly transported, stored and subjected to heat treatment. Increasing awareness and creation of the hygienic practice of camel milk handling is paramount. Antibiotics should only be used to treat sick animals based on the diagnosis of the diseases (Supplementary Information).